试论经国家认证的新加坡华人性叙事: “南洋”、“新谣”与 “Singapo 人” = State endorsed narratives of Singaporean Chineseness: 'Nanyang', ‘Xinyao’ and ‘Singapo 人’ - 卓佳惠 Tho, Jia Hui (Nanyang Technological University, 2023)
新加坡华人性的独特性一直备受广泛关注。许多研究指出，新加坡华人性的权威性叙事是由国家单方面建构的，用于塑造或引导国家认可的新加坡性。本文意识到，相关叙事未必是国家单方面的建构并强加于人民，而是基于或借鉴草根现实，随后被国家认证和挪用来标志新加坡独特的华人性。此外，本文还发现，这些有草根背景的华人性叙事是在 1990 年代以后被关注，并在约 2015 年被国家认证和挪用。因此，本文将研究对象锁定在三种经国家认证的新加坡华人性叙事——“南洋”、“新 谣”与 “Singapo 人"，旨在探究国家如何以及为何认证、挪用或支持这些叙事。希望 从不同的角度探讨并补充学界对新加坡现代(1990 年后)华人性研究。Singaporean Chineseness has been widely recognized for its uniqueness. Numerous studies have highlighted that state unilaterally constructs the authoritative narrative of Singaporean Chineseness, in order to shape or steer the Chinese Singaporean identity towards a state-recognized one. However, this thesis acknowledges that the relevant narratives may not necessarily be a unilateral construction imposed on the people by the state. Rather, they are based on or borrowed from grassroots narratives or concepts and subsequently endorsed and appropriated by the state to label the unique Singaporean Chineseness. Furthermore, this thesis reveals that the narratives of Singaporean Chineseness originating from the grassroots have garnered significant attention since the 1990s, and were officially endorsed and appropriated by the state in approximately 2015. Therefore, this article studies three state endorsed narratives of Singaporean Chineseness, "Nanyang," "Xinyao," and "Singapo 人," to investigate the state's endorsement, appropriation, or support of these narratives. By offering a different perspective, this research aims to enrich academic research on modern Singaporean Chineseness, particularly from the post-1990s era.